Standardization and Standard Essential Patents for Public Good: Application in Automotive Industry - Soumya Prakash Patra; K. D. Raju (Faculty of Law, Universitas Pattimura, 2021)
The majority of patents related to automotive safety systems are owned by a limited number of companies. Absorption and implementation of such innovations in large markets require solutions that would go beyond what is protected through exclusive means viz. patents. Taking learnings from the field of communication, wherein by implementing what is known as standard-essential patents, a horizontal deployment of a similar concept is required in other areas, most notably, automotive safety systems is necessitated. This study aims to explore the need for a practical approach to a broader technological, commercial, and social cause.